Strategi Pengembangan Usaha dalam mengenalkan UMKM “Renyah Kepiting Borneo” melalui Pembuatan Video Profil Usaha dan Inovasi Produk dalam meningkatkan Daya Saing UMKM di Sentra Industri Kecil, Teritip Balikpapan - Berlianti, Nadya; Darrens, Andreans Figo; Sa’idah, Elly; Sari, Intan Sapitri Permata; Jaya, M. Rifki Refian; Prihanisetyo, Adi (Fokus ABDIMAS, 2024)
Field Work Practice (PKL) or also known as Innovation Development (PI) is a service activity of STIE Madani students to the community, especially to Micro, Small and Medium Enterprises (MSMEs). On this occasion, group 11 PI students of STIE Madani Balikpapan provided assistance in one of the villages in Balikpapan City, namely Teritip Village. The target of MSMEs targeted in the Innovation Development Program (PI) this time is the "Renyah Borneo Crab" MSME located in the Teritip Small Industry Center. The objectives of the Innovation Development activities are: 1) Assisting in assisting the processing of innovative products from "Renyah Borneo Crab"; 2) Assisting in making product packaging sticker designs; 3) Assisting in making business profile videos; 4) Assisting in providing knowledge about digital marketing through seminar activities with marketing themes and moving bookkeeping from manual to digital. Keywords: MSMEs, Innovation Development, Renyah Borneo Crab, Teritip Village, Balikpapan, STIE Madani.